Copper oxide hierarchical morphology derived from MOF precursors for enhancing ethanol vapor sensing performance. Issue 28 (29th June 2020) - Wang, Sha; Gao, Zhimin; Song, Guoshuai; Yu, Yantao; He, Wenxiu; Li, Linlin; Wang, Tieqiang; Fan, Fuqiang; Li, Yunong; Zhang, Liying; Zhang, Xuemin; Fu, Yu; et al.
Abstract : The structure–function relationship of CuO hierarchical morphologies in gas sensing has been revealed. Abstract : Building CuO hierarchical structures with precisely controlled micro/nano scale features remains a great challenge, although this plays a vital role in optimizing their performance in specific applications, such as gas sensing. Herein, two CuO hierarchical morphologies have been successfully prepared via the pyrolysis of different metal–organic framework (MOF) precursors with similar chemical compositions but different morphologies. The relationship between MOF precursors and micro- and nano-scale structural features of the yielded hierarchical structures has been revealed in detail. The micro scale feature of the cube-like MOF is easier to retain than that of the rod-like MOF after pyrolysis. The nanoscale feature of the obtained CuO hierarchical structures is determined by the size of the MOF precursor structure in the radial direction. In addition, the obtained two CuO hierarchical morphologies exhibited better gas sensing performance than the other CuO morphologies because of their structural stability and porosity. Meanwhile, the sensors with rod-like CuO hierarchical morphology display better sensing performance than the cube-like CuO sensors because of the synergistic effect of the micro and nano scale structural features in rod-like CuO, shedding light on the structure–function relationship of CuO hierarchical morphologies in gas sensing.